2016
DOI: 10.1088/0953-4075/49/24/245601
|View full text |Cite
|
Sign up to set email alerts
|

Classical chaos and harmonic generation in laser driven nanorings

Abstract: A quantum ring driven by an intense laser field emits light in the form of high-harmonic radiation resulting from the strong acceleration experienced by the active electrons forced to move on a curved trajectory. The spectrum of the emitted light is rich and strongly dependent on the parameters of the problem. In order to investigate the physical origin of such variability, we focus on the seemingly simple problem of a laser-driven charge constrained to a ring from a classical standpoint. As it turns out, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…As mentioned in the Introduction, a plethora of schemes, requiring the presence of a magnetic field, has been advanced to overpass the problem. Rings and annuli are perfectly suitable to be used with a magnetic field because of their circular symmetry; they provide a fundamental environment for basic and applicative use [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Now, we discuss the problem of the annulus crossed by an orthogonal static magnetic field B 0 .…”
Section: Static Magnetic Fieldmentioning
confidence: 99%
“…As mentioned in the Introduction, a plethora of schemes, requiring the presence of a magnetic field, has been advanced to overpass the problem. Rings and annuli are perfectly suitable to be used with a magnetic field because of their circular symmetry; they provide a fundamental environment for basic and applicative use [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Now, we discuss the problem of the annulus crossed by an orthogonal static magnetic field B 0 .…”
Section: Static Magnetic Fieldmentioning
confidence: 99%
“…However, for the particular problem dealt with now, deeper insight can be gained by studying the classical counterpart of the laser driven ring: it has been shown that the Newton equation of motion of a charge bound on a circle has a chaotic nature and this fact produces a signature in quantal calculations in the form of line broadening and noise. 32,33 To introduce the concept of time evolution of the spectrum, we resort to a Morlet wavelet analysis. The Morlet wavelet is dened as:…”
Section: Numerical Simulationsmentioning
confidence: 99%